The Role of Fundamental Strategies in Overcoming the Inflation - Erwin Permana; Nuruddin Subhan; Juliana Juliana; Muhammad Abduh (KEDJATI Journal of Islamic Civilization, 2024)
High inflation rates are a complex economic challenge and have far-reaching impacts. To deal with these problems, an effective strategy involving a series of policy instruments and a deep understanding of the root problems that cause inflation is needed. This research aims to analyze strategies to overcome inflation and offer fundamental strategies. This research uses a qualitative with a descriptive-analytical method. The research data is obtained through a literature review: the relevant information from previous research results or official publications. The research results show that it is more supply-side based on analyzing the government's strategy for overcoming inflation. Based on examining the existing situation, this strategy must be complemented by a demand side: providing energy subsidies, increasing national production capacity, and moral education. Based on an in-depth study of inflation, this research provides recommendations for a more fundamental strategy in integrating financial technology (fintech) with precious metals (gold-fintech). This condition means gold-based fintech. It means realizing practical transactions using fintech, which is flexible, practical, and cashless, but the standard is using gold, not fiat money. Also, Islam views gold and silver as suitable for currency use. Apart from internal factors and conformity between nominal and intrinsic value, the uses of gold and silver are based on the sharia. Gold and silver are strong enough to withstand inflation, something that paper money-based currencies do not have. Hence, researchers suggest further research regarding the technical transition mechanism from fiat money-based to precious gold and metal-based fintech.